Corona Virus and Kidney Failure: A review - Zahraa Kareem Al-Mayali; Shaymaa Al-Jaafari (Kufa Journal for Nursing Sciences)
Coronavirus disease (COVID-19) is a life-threatening and  highly infectious disease. It impacts several body organs for example the lungs, kidneys, blood texture and contents, digestive cannel, and heart. The first case emerged in China and rapidly spreading and affirmed a global pandemic. COVID-19 is a major threat and a pandemic all over the world. Severe Acute Respiratory Syndrome Corona Virus2, the cause of coronavirus disease 19, connects to its target cells utilizing  (ACE2),  Angiotensin Converting Enzyme 2which can be stated via epithelial cells of numerous organs. Corona Virus can basis reasonable or harsh kidney damage with signs involving proteinuria, hematuria, eminent urea nitrogen, and creatinine. The kidney cell contain ACE2 receptors that allow to Corona Virus 2 to join it , attack , duplicate and potentially destroy all tissue